Sistem Informasi Hukum dengan Perizinan Perumahan untuk Proses Efisiensi Administrasi: Sistem Informasi Hukum dengan Perizinan Perumahan untuk Proses Efisiensi Administrasi - SAYUTI, Akhmad; Krisna, Robi; Efniar; Triana, Dora Indah (Fakultas Ilmu Komputer, 2025)
The housing permit administration process often encounters challenges such as bureaucratic complexity, long processing times, and poor information integration between systems. These issues create inefficiency, data overlap, and limited transparency. To address this, this study aims to integrate legal information systems with the housing permit process through the development of a web-based platform. The proposed system synchronizes legal data related to housing regulations with administrative mechanisms, enabling faster and more reliable services. The research applies the Waterfall method, consisting of needs analysis, system design, implementation, testing, and maintenance. The system is designed with key features, including online permit applications, automatic validation of legal documents, real-time application tracking, and digital document archiving. These functions provide applicants and agencies with better access to information, while ensuring that legal and administrative aspects remain aligned with regulatory provisions. Case study implementation demonstrates that system integration can reduce processing time, minimize administrative errors, and accelerate decision-making. Additionally, the platform enhances transparency by allowing applicants to monitor their application status directly, thereby fostering accountability in public administration. The results highlight that digital transformation in housing permit services not only improves efficiency but also strengthens legal certainty and administrative order. This approach contributes significantly to optimizing governance in regional development and can serve as a model for other digital permit systems within the government sector. Ultimately, the integration of technology and legal frameworks creates a more efficient, transparent, and accountable housing permit process.